If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9j + 12k + -3p = 0 Solving 9j + 12k + -3p = 0 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-12k' to each side of the equation. 9j + 12k + -12k + -3p = 0 + -12k Combine like terms: 12k + -12k = 0 9j + 0 + -3p = 0 + -12k 9j + -3p = 0 + -12k Remove the zero: 9j + -3p = -12k Add '3p' to each side of the equation. 9j + -3p + 3p = -12k + 3p Combine like terms: -3p + 3p = 0 9j + 0 = -12k + 3p 9j = -12k + 3p Divide each side by '9'. j = -1.333333333k + 0.3333333333p Simplifying j = -1.333333333k + 0.3333333333p
| y^-9/y^-6 | | -2t^3+12t^2+32t=0 | | x+252=3x | | 24n=13m+19 | | 4(9+3x)-12=16 | | 6(4x+2)+3(2x+3)+5=30x+27 | | 5X-2X+7=X+2 | | F(x)=4-5y | | 1622/180 | | f(n)=2.5+3(n-1) | | 1620/180 | | p*2.90=2.1 | | 4XY=80.8 | | 5(2x+2)+4(5x+6)+6=30x+41 | | 25m^7n^2^p^3/5m^5n^8 | | c*2.4=14.8 | | 5x^2+4x=2x+6 | | 2x+0= | | 5x^2+4x=2x+3 | | -4x-7=2x+5 | | 4a+2b+a+b= | | 2(x-7)+1=-3(x-1) | | -4x-7=2f+5 | | 11k-17-8=6k | | 5(-3x+4)-24=5(-3x-4)+16 | | y=4(2)x | | 3(x-1)-4x=2(x+4)-4 | | 1800=(n*2)*180 | | 5x-4=14x-37 | | (-5y+8)(-5y+4)= | | 5(3x+1)=-4(2x-3) | | k/21=7/3 |